Religiosidade jovem no extremo leste da capital de São Paulo: implicações da religiosidade no cotidiano da juventude da Assembléia de Deus no bairro de São Miguel Paulista - Souza, Eli Cassiano de (2012)
This research is the result of inquiries made from how the Church looks to their young, and how this look helps them to engage and to relate in the society in which they live. When we investigate a church, which became Centennial in our country, the Assembly of God, we sought to understand what, from its formation, consolidation and institutionalization, she manages to preserve its origins in the present day. From a case study in the Assembly of God in the neighborhood of São Miguel Paulista, we analyze the relationship of the Church with its history and check what are the traits that remain and those that changes. The Study of a local church, allowed us to understand, from the existing social relations in the periphery, that the changes seem to happen more slowly and, therefore, the amount of breaks and generally smaller than those occurring in urban centres and in higher economic classes. On the other hand, there are breaks, questions and even dissatisfaction from those who are capable, which make the churches suffer modifications and the searched church is no exception to this rule. Although there is a strong tradition in the Church of the periphery area, this also begins to look for their young and realize that to keep them, it needs to serve them. But it is in the form of care, however, that we find a dichotomy, where the perception of the need for change, is also present, the very effort to stay. Given this, we saw a church which, it seems to us, seek to integrate the young within it, but it still failed to do so with the society, and a youth that despite point to the importance of social integration, seems more concerned to leave the Church and society also separated